2021
DOI: 10.3389/fendo.2021.572690
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Hyaluronic Acid Hydrogels as a Carrier for Constant-Release Clenbuterol Against High-Fat Diet-Induced Obesity in Mice

Abstract: The global obesity population is increasing year-by-year, and the related cost is sharply increasing annually. There are several methods available to combat obesity; however, there is a lack of a single tool that is both safe and efficacious. The use of Clenbuterol in bodybuilding and by professional athletes is controversial owing to its side effects, including hepatotoxicity. This study administered Clenbuterol at a much lower dose than the established safety level, and rather than through oral administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Hyaluronic acid found to have indirect role in controlling obesity by developing a modern and hopeful manner to fight obesity through a single, monthly controlled-release intra adipose dose of "Clenbuterol-modified HA thermo-sensitive hydrogel", the recently established "Clenbuterol formula" found to be effective not only in reducing body weight but also in managing the side effects of the classical oral administration of "Clenbuterol" alone [52].…”
Section: Effect Of Polymers Adorned Aunps On Biological Parametersmentioning
confidence: 99%
“…Hyaluronic acid found to have indirect role in controlling obesity by developing a modern and hopeful manner to fight obesity through a single, monthly controlled-release intra adipose dose of "Clenbuterol-modified HA thermo-sensitive hydrogel", the recently established "Clenbuterol formula" found to be effective not only in reducing body weight but also in managing the side effects of the classical oral administration of "Clenbuterol" alone [52].…”
Section: Effect Of Polymers Adorned Aunps On Biological Parametersmentioning
confidence: 99%
“…The cell viability, cytotoxicity, and cell death rate of the specimen were evaluated by water-soluble tetrazolium salt-1 assay (WST-1 assay), lactate dehydrogenase (LDH) assay, and live/dead staining, [28][29][30] respectively.…”
Section: Biocompatibility Of Tamentioning
confidence: 99%
“…Obesity is a result of energy imbalance caused by changes in diet and physical activity as well as excessive body fat accumulation (Kang et al, 2016;Chen and Lin, 2021). Previous studies have demonstrated that obesity is associated with an increased risk of cardiovascular disease, type 2 diabetes, hypertension, and fatty liver disease as well as increased mortality (Hotamisligil, 2006;Saltiel and Olefsky, 2017).…”
Section: Introductionmentioning
confidence: 99%